Conditions, mechanisms of transition from the “Advanced professional development” paradigm to the “Continuous professional development of teachers” paradigm (Journal of Educational Sciences, 2024)
In this article, the scientifically based situation, mechanism and resource transition from the paradigm of professional development to the paradigm of continuous professional development of the teacher. The most important condition for ensuring the quality of education in the conditions of updating the content of education at all levels of the educational system of Kazakhstan is the constant professional development of the teacher. In this regard, in this article, the state of passing PUKP is considered as an actual problem at the present time. The purpose of the study is to scientifically substantiate the conditions, mechanisms and resources of the transition from the paradigm of “advanced training” to the paradigm of “continuous professional development of a teacher.” Research methods: content analysis, comparative analysis, theoretical analysis. Result of the study: based on conceptual approaches, an analytical report was compiled on the scientific substantiation of the reasons for the transition from the paradigm of “advanced training” to the paradigm of “continuous professional development of teachers”; from a comparative point of view, the international and Kazakhstani experience of introducing the paradigm of “professional development” into the paradigm of “continuous professional development of a teacher” and “continuous professional development of a teacher” has been studied. Scope of application: secondary education system; professional pedagogical education, postgraduate pedagogical education, additional professional pedagogical education; system of professional development of teaching staff. Key words: continuing teacher education, professional development of teachers, continuous professional development of teachers.